Mitochondrial DNA Copy Number Variations and Serum Pepsinogen Levels for Risk Assessment in Gastric Cancer - Alikhani, Mehdi; Saberi, Samaneh; Esmaeili, Maryam; Michel, Valérie; Tashakoripour, Mohammad; Abdirad, Afshin; Aghakhani, Arezoo; Eybpoosh, Sana; Vosough, Massoud; Mohagheghi, Mohammad Ali; Eshagh Hosseini, Mahmoud; Touati, Eliette; et al. (Iranian biomedical journal, 2021)
Variations in mitochondrial DNA copy number (mtDNA-CN) of peripheral blood leukocytes (PBLs), as a potential biomarker for gastric cancer (GC) screening has currently been subject to controversy. Herein, we have assessed its efficiency in GC screening, in parallel and in combination with serum pepsinogen (sPG) I/II ratio, as an established indicator of gastric atrophy. The study population included GC (n = 53) and non-GC (n = 207) dyspeptic patients. The non-GC group was histologically categorized into CG (n = 104) and NM (n = 103) subgroups. The MtDNA-CN of PBLs was measured by quantitative real-time PCR. The sPG I and II levels and anti-H. pylori serum IgG were measured by ELISA. The mtDNA-CN was found significantly higher in GC vs. non-GC (OR = 3.0; 95% CI = 1.4, 6.4) subjects. Conversely, GC patients had significantly lower sPG I/II ratio than the non-GC (OR = 3.2; CI = 1.4, 7.2) subjects. The combination of these two biomarkers yielded a dramatic amplification of the odds of GC risk in double-positive (high mtDNA-CN-low sPGI/II) subjects, in reference to double-negatives (low mtDNA-CN-high sPGI/II), when assessed against non-GC (OR = 27.1; CI = 5.0, 147.3), CG (OR = 13.1; CI = 2.4, 72.6), or NM (OR = 49.5; CI = 7.9, 311.6) groups. The combination of these two biomarkers, namely mtDNA-CN in PBLs and serum PG I/II ratio, drastically enhanced the efficiency of GC risk assessment, which calls for further validations.